2019
DOI: 10.1002/mame.201900169
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of Shape‐Memory Aerogel Based on Chitosan/Poly(ethylene glycol) Diacrylate Semi‐Interpenetrating Networks via a Facile and Eco‐Friendly Strategy

Abstract: exhibit strong advantages in providing diverse mechanical properties, such as varying from stiff to high elasticity to enable adaption to a wide range of demands.While the application of aerogels in smart materials has attracted increasing attention, ensuring full functionality in a porous structure is still highly challenging. As one of the booming smart materials, shape-memory polymers (SMPs) have been intensively investigated, and numerous multiresponsive, [20][21][22][23][24][25] multifunctional shape memo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…Since Rowan reported the first thermal-responsive SMPA material with the capabilities of shape fixation and shape recovery in 2016, [8] many research groups have focused on this field and reported a series of novel SMPAs originating from traditional shape memory polymeric materials. [9][10][11][12] A significant commonality of these previous reported SMPA materials is that they can only perform a one-way shape-memory deformation. As shown in Figure 1a, the one-way SMPAs (1W-SMPA, permanent shape 1) were first deformed at a relatively high temperature (usually higher than their glass transition or melting temperatures) and then cooled back to room temperature to obtain a temporary shape (temporary shape 2).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since Rowan reported the first thermal-responsive SMPA material with the capabilities of shape fixation and shape recovery in 2016, [8] many research groups have focused on this field and reported a series of novel SMPAs originating from traditional shape memory polymeric materials. [9][10][11][12] A significant commonality of these previous reported SMPA materials is that they can only perform a one-way shape-memory deformation. As shown in Figure 1a, the one-way SMPAs (1W-SMPA, permanent shape 1) were first deformed at a relatively high temperature (usually higher than their glass transition or melting temperatures) and then cooled back to room temperature to obtain a temporary shape (temporary shape 2).…”
Section: Introductionmentioning
confidence: 99%
“…Since Rowan reported the first thermal‐responsive SMPA material with the capabilities of shape fixation and shape recovery in 2016, [ 8 ] many research groups have focused on this field and reported a series of novel SMPAs originating from traditional shape memory polymeric materials. [ 9 , 10 , 11 , 12 ]…”
Section: Introductionmentioning
confidence: 99%
“…22–24 In addition, the fabrication of aerogels is feasible because the internal pores can be easily tuned by adjusting the concentration of precursors as well as freeze-drying parameters, such as temperature, pressure, and even the freeze direction. 25–27 However, current aerogels always lack shape-shifting capacity. 28,29 Shape-memory polymers are emerging nature-inspired stimuli-responsive materials with the capacity to recover to their original geometry from an arbitrary temporary shape generated by elaborately programming upon a certain external stimulus, such as heat, light, and chemicals, and of course, the so-called shape-memory effect.…”
Section: Introductionmentioning
confidence: 99%
“…[24] A thermally induced SMP aerogel based on CH/poly (ethylene glycol) diacrylate has been produced using an eco-friendly strategy wherein the interpenetrated CH acts as the main network to enhance the aerogel skeleton. [25] Remote and contactless controllability of shape recovery kinetics has been demon-strated for CH/rGO strips cross-linked with ethylene glycol diglycidyl ether at pH 10.5 by changing the light intensities. [26] From the above references, it is evident that mostly CH has been added as a filler or used for modifying the surfaces.…”
Section: Introductionmentioning
confidence: 99%
“…A polycaprolactone based toughened shape memory polyurethane biocomposite exhibited an ultimate tensile strength of 5.2 MPa, and its composite containing 10 % nano CH flakes showed an ultimate tensile strength of 12 MPa [24] . A thermally induced SMP aerogel based on CH/poly (ethylene glycol) diacrylate has been produced using an eco‐friendly strategy wherein the interpenetrated CH acts as the main network to enhance the aerogel skeleton [25] . Remote and contactless controllability of shape recovery kinetics has been demonstrated for CH/rGO strips cross‐linked with ethylene glycol diglycidyl ether at pH 10.5 by changing the light intensities [26] …”
Section: Introductionmentioning
confidence: 99%